2006
DOI: 10.1042/cs20050361
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous hydration with a 2.5% glucose solution in Type II diabetes

Abstract: Physicians are often unclear about how fast intravenous glucose solutions should be administered to adequately hydrate patients with Type II diabetes while avoiding hyperglycaemia and excessive plasma volume expansion. The aim of the present study was to analyse the disposition of a 2.5% glucose solution and create a nomogram which could serve as a guide to fluid therapy in these patients. Twelve males (mean body mass index, 29 kg/m(2)) with Type II diabetes due to insulin resistance, as quantified by an eugly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Hence, the size of the body fluid space expanded by the infused volume could not have been larger than the plasma volume. This finding is not intuitive but is in agreement with previous kinetic studies based on IV infusion of isotonic glucose solutions in healthy volunteers [6, 9] and in surgical [7] and diabetic [10] patients.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the size of the body fluid space expanded by the infused volume could not have been larger than the plasma volume. This finding is not intuitive but is in agreement with previous kinetic studies based on IV infusion of isotonic glucose solutions in healthy volunteers [6, 9] and in surgical [7] and diabetic [10] patients.…”
Section: Discussionsupporting
confidence: 91%
“…This promotes a slower restoration of the plasma glucose curve after infusion than indicated by the actual metabolism. This large V d might possibly be an effect of epidural analgesia, but we have recently observed a similarly large V d , almost corresponding to the expected size of the ECF space, in diabetes type II patients (15). These results suggest the existence of physiological and metabolic conditions in which V d for exogenous glucose becomes markedly larger than in healthy volunteers.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies, however, conducted mainly on sheep, indicate that the kinetic parameters are fairly robust within clinical feasible limits [23,24]. Furthermore, it has been shown that the kinetic parameters may be used for controlling infusion rate, in order to achieve a pre-determined target dilution [25].…”
Section: Discussionmentioning
confidence: 97%